Political Education in Formal Institutions: Strategies to Increase Public Participation in the Democratic Era - Franciscus Xaverius Wartoyo; Ginting, Yuni Priskila (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2025)
Political education in formal institutions plays a vital role in shaping citizens who are aware of their rights and obligations and encourage active participation in democratic life. This study aims to analyses political education strategies implemented in formal educational institutions, especially in universities, in order to increase public participation in the era of democracy. The research method used is the normative method with a conceptual approach and a regulatory approach. The results of the study indicate that political education can be instilled through curriculum strengthening, citizenship training, open discussion forums, and the integration of information technology as a means of political learning. However, various challenges are still faced, such as limited resources, structural barriers, and low academic freedom in some institutions. Therefore, a comprehensive and collaborative strategy is needed between educational institutions, the government, and civil society to create an inclusive, critical, and sustainable political education environment. Thus, political education in formal institutions can be a catalyst in shaping active and responsible public participation in the era of democracy.